How India Clothed the World The World of South Asian Textiles, 1500-1850 (Volume 4) - Riello, Giorgio; Roy, Tirthankar (Brill, 2009)
Cloth has always been the most global of all traded commodities. It is an illuminating example of the circulation of goods, skills, knowledge and capital across wide geographic spaces. South Asia has been central to the making of these global exchanges over time. This volume presents innovative research that explores the dynamic ways in which diverse textile production and trade regions generated the 'first globalization'. A series of experts connect this global commodity with the dramatic political and economic transformations that characterised the Indian Ocean in the seventeenth and eighteenth centuries. Collectively, the essays transform our understanding of the contribution of South Asian cloth to the making of the modern world economy.